(6r-7s+8t)-(2r-3s+4t)=

Simple and best practice solution for (6r-7s+8t)-(2r-3s+4t)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6r-7s+8t)-(2r-3s+4t)= equation:


Simplifying
(6r + -7s + 8t) + -1(2r + -3s + 4t) = 0

Remove parenthesis around (6r + -7s + 8t)
6r + -7s + 8t + -1(2r + -3s + 4t) = 0
6r + -7s + 8t + (2r * -1 + -3s * -1 + 4t * -1) = 0
6r + -7s + 8t + (-2r + 3s + -4t) = 0

Reorder the terms:
6r + -2r + -7s + 3s + 8t + -4t = 0

Combine like terms: 6r + -2r = 4r
4r + -7s + 3s + 8t + -4t = 0

Combine like terms: -7s + 3s = -4s
4r + -4s + 8t + -4t = 0

Combine like terms: 8t + -4t = 4t
4r + -4s + 4t = 0

Solving
4r + -4s + 4t = 0

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '4s' to each side of the equation.
4r + -4s + 4s + 4t = 0 + 4s

Combine like terms: -4s + 4s = 0
4r + 0 + 4t = 0 + 4s
4r + 4t = 0 + 4s
Remove the zero:
4r + 4t = 4s

Add '-4t' to each side of the equation.
4r + 4t + -4t = 4s + -4t

Combine like terms: 4t + -4t = 0
4r + 0 = 4s + -4t
4r = 4s + -4t

Divide each side by '4'.
r = s + -1t

Simplifying
r = s + -1t

See similar equations:

| -7.70=10.8-7.4t | | 24+3n=24+1.5 | | 2x^3-7x^2-8x+28=0factoring | | 5d^2+9d-18=0 | | 7.9a+3.25=-14.13 | | 6x-1+7x=90 | | 7.9a+3.25=-14.1 | | 2x-9y=8 | | 4y=-6x-2 | | X^2-4ix-13=0 | | 6(d+6)-8=2*d+30 | | -51.98=7.7x+5 | | X^2+12=-18 | | (1/2)c=5 | | -1/6z=-4.5 | | 50+90t-4.9t^2=250 | | 3/4-6/8= | | 5.7+1.2n=3.06 | | 8.3y-9.8=13.44 | | 22.1/0.5= | | 3d^2-8d-11=0 | | 6/11p=-12/11 | | (x^3+8)(x^2+5x)=0 | | x^2+48x-1024=0 | | x+26.7=7.1 | | 27+s=23 | | 3x^2-2n-8= | | 3m^2+2m-1=0 | | x-11=-2x-5 | | -(18+15)=-18+(-15) | | 1.5x-12=3x/4 | | y=9x^2+12x+3 |

Equations solver categories